Application of orange essential oil as an antistaphylococcal agent in a dressing model - Muthaiyan Arunachalam; Biswas Debabrata; Crandall Philip G; Wilkinson Brian J; Ricke Steven C (BMC, 2012)
Abstract Background Staphylococcus aureus is the pathogen most often and prevalently involved in skin and soft tissue infections. In recent decades outbreaks of methicillin-resistant S. aureus (MRSA) have created major problems for skin therapy, and burn and wound care units. Topical antimicrobials are most important component of wound infection therapy. Alternative therapies are being sought for treatment of MRSA and one area of interest is the use of essential oils. With the increasing interest in the use and application of natural products, we screened the potential application of terpeneless cold pressed Valencia orange oil (CPV) for topical therapy against MRSA using an in vitro dressing model and skin keratinocyte cell culture model. Methods The inhibitory effect of CPV was determined by disc diffusion vapor assay for MRSA and vancomycin intermediate-resistant S. aureus (VISA) strains. Antistaphylococcal effect of CPV in an in vitro dressing model was tested on S. aureus inoculated tryptic soya agar plate. Bactericidal effect of CPV on MRSA and VISA infected keratinocyte cells was examined by enumeration of extra- and intra-cellular bacterial cells at different treatment time points. Cytotoxic effects on human skin cells was tested by adding CPV to the keratinocyte (HEK001) cells grown in serum free KSFM media, and observed by phase-contrast microscope. Results CPV vapour effectively inhibited the MRSA and VISA strains in both disc diffusion vapour assay and in vitro dressing model. Compared to untreated control addition of 0.1% CPV to MRSA infected keratinocyte decreased the viable MRSA cells by 2 log CFU/mL in 1 h and in VISA strain 3 log CFU/mL reduction was observed in 1 h. After 3 h viable S. aureus cells were not detected in the 0.2% CPV treatment. Bactericidal concentration of CPV did not show any cytotoxic effect on the human skin keratinocyte cells in vitro. Conclusions At lower concentration addition of CPV to keratinocytes infected with MRSA and VISA rapidly killed the bacterial cells without causing any toxic effect to the keratinocytes. Therefore, the results of this study warrant further in vivo study to evaluate the potential of CPV as a topical antistaphylococcal agent.